Der lateinische ›Alexanderroman‹ des Iulius Valerius Sprache, Erzählung, Kontext - Wulfram, Hartmut (Millennium-Studien / Millennium Studies, 2023)
Within the scope of the Greek-Latin Alexander romance, the Res gestae Alexandri Macedonis by Julius Valerius (early fourth century CE) stand out due to their high literary and stylistic standards. The eleven contributions in this edited volume primarily focus on issues of narrative technique, linguistic design, and intertextuality, thereby illustrating the unique features and rank of this often-neglected work in literary history.